(untitled) (Research, Society and Development, 2020)
The tiririca extract (Cyperus rotundus) has been shown to be a possible promoter in the rooting of cuttings and as improvement of the quality of roots, for having substances that act synergistically to auxin indole-3-acetic acid (IAA). Thus, this work aimed to evaluate the efficiency of concentrations of aqueous extract of nutsedge tubers in the rooting of Semi-hardwood cuttings of mini ixora (Ixora coccínea), a plant species considered difficult to root. The experimental design used was completely randomized, with five treatments, which were composed by the combination of concentrations of aqueous extract (zero; 25; 50; 75 and 100%), prepared by grinding the tubers of tiririca in distilled water. As used cuttings were standard with 15 cm in length, being immerse for 10 minutes in the extract, according to the requirements of each treatment and conditioned in plastic bags specified substrate sand in nursery. The cuttings were evaluated at 30, 60, 90 and 120 days after the experiment installation, in 10 replications per treatment, considering the percentage of survival cuttings; Percentage of rooted cuttings; Percentage of mortality; Average length of roots (cm); and Fresh mass and Dry mass of roots (g). The variance analysis revealed that there were significant effects between the concentrations of aqueous nutshell extract and the length of the root, and at 30 days, there was a linear reduction in the fresh weight of the root as the concentrations of the extract increased, and at 60 days, there was an increase to 50% in the concentration. There was no significant difference for the other parameters evaluated.